Pengaruh Influencer Marketing, Online Customer Review, dan Price Bundling Terhadap Keputusan Pembelian Produk Skincare Melalui Media Tiktok - Komang Tania Andini; I Nengah Wirsa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the influence of online customer review and price bundling influencer marketing partially and simultaneously on purchasing decisions. The sample in this study was 112 people who had purchased or seen Yoni skincare promotions on TikTok, with a minimum age criteria of 20 years to > 40 years. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, it was found that motivation had a positive and significant effect on purchasing decisions, online customer reviews had a positive and significant effect on purchasing decisions, price bundling had a positive and significant effect on purchasing decisions and online customer review and price bundling influencer marketing together had a significant effect on purchasing decisions. The researcher's recommendations include encouraging Yoni Skincare management to consistently guide collaborating influencers to provide honest product reviews, offering prizes or discounts to consumers who provide strong and convincing reviews, consistently offering useful and high-quality product bundles, and continuously innovating to deliver higher-quality products.